Responses of a Mutant Strain of Chlamydomonas reinhardi to Prolonged Organotrophic Growth - Hudock, G. A. (1967)
The responses of the wild type strain and of the y-2 mutant strain of Chlamydomonas reinhardi to long term organotrophic growth were studied. It was shown that wild type can be cultured as an organotroph for at least a month with little decrease in chlorophyll content and no loss of viability. On the other hand, the mutant strain y-2 dies during such organotrophic growth, death beginning after 5 to 6 days in the dark. The kinetics of death indicate that the loss of 95% of the chlorophyll precedes death and that revertants to wild type overgrow such a culture. The results suggest that death of y-2 is correlated with the loss of chlorophyll rather than simple metabolic response to organotrophy and that the chloroplast or a chloroplast related factor may perform certain nonphotosynthetic functions in C. reinhardi. The activities of nicotine adenine dinucleotide and nicotine adenine dinucleotide phosphate dependent triose phosphate dehydrogenases were studied during long term organotrophic growth of y-2. It was found that the activities of these enzymes varied in a manner consistent with previous findings under these conditions. The activity of glutamic dehydrogenase was found to vary as a function of chlorophyll content in the mutant strain y-2.